Association of alcohol abstinence with risk of hyperuricemia in rural Chinese adults: the Henan Rural Cohort Study - Xiaokang Dong; Lulu Zhang; Ning Kang; Huanxiang Zhang; Wei Liao; Xiaotian Liu; Pengling Liu; Lei Yin; Chongjian Wang (BMC Public Health)
Abstract Background Alcohol drinking can cause hyperuricemia (HUA), but few studies have explored alcohol abstinence’s health effects, particularly the abstinence duration on HUA. This study aimed to evaluate the associations of abstinence with HUA in rural Chinese adults. Methods This was a cross-sectional study of 38,855 participants (15,371 males and 23,484 females) using the baseline data (2015–2017) from the Henan Rural Cohort Study. A questionnaire survey collected information on alcohol consumption patterns. Multivariate logistic regression analyses were used to evaluate the associations of type of alcoholic beverages, abstinence status and abstinence duration with HUA, respectively. Restricted cubic spline models were applied to visualize the dose-response trend of HUA risk with increasing abstinence duration. Results 3,978 cases of 38,855 participants were identified with HUA. Total alcohol intake, including beer, liquor and rice wine intake was significantly associated with the increased risk of HUA, especially for male participants. Compared with current drinkers, former drinkers and non-drinkers presented lower ORs (95%CIs) of 0.686 (0.676, 0.844) and 0.718 (0.649, 0.793) for HUA. Furthermore, the aORs (95%CIs) for those former drinkers with < 5, 6–10 and ≥ 11 years abstinence duration were 0.868 (0.693, 1.086), 0.753 (0.519, 1.092) and 0.717 (0.517, 0.990), respectively. In addition, the risk of HUA decreased with the increasing years of abstinence duration (P for trend < 0.050) and negative linear dose-response associations were observed. Conclusion Former drinkers were associated with a reduced risk of HUA compared with current drinkers. Moreover, sustained alcohol abstinence could be beneficial for preventing HUA. Clinical Trial Registration The Henan Rural Cohort Study was registered on the Chinese Clinical Trial Register (Registration number: ChiCTR-OOC-15006699). Date of registration: 2015-07-06 http://www.chictr.org.cn/showproj.aspx?proj=11375 .